2001
DOI: 10.1074/jbc.m007601200
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Activates Hyaluronan Synthase 2 in Epidermal Keratinocytes and Increases Pericellular and Intracellular Hyaluronan

Abstract: Hyaluronan is an abundant and rapidly turned over matrix molecule between the vital cell layers of the epidermis. In this study, epidermal growth factor (EGF) induced a coat of hyaluronan and a 3-5-fold increase in its rate of synthesis in a rat epidermal keratinocyte cell line that has retained its ability for differentiation. EGF also increased hyaluronan in perinuclear vesicles, suggesting concurrent enhancement in its endocytosis. Cell-associated hyaluronan was most abundant in elongated cells that were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
144
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(156 citation statements)
references
References 56 publications
12
144
0
Order By: Relevance
“…In addition, cell surface protrusions make contacts to extracellular matrix and other cells, sense and interact with the environment, and lead to new attachment sites and cell migration (1). Hyaluronan synthesis increases the migration rate of different cell types (17)(18)(19), but it is currently not known which type of protrusions are involved. The present finding that hyaluronan tethered to plasma membrane strongly promotes cell surface protrusions offers a novel view to a number of previous reports indicating that hyaluronan stimulates cellular locomotion, multidrug resistance, ErbB2 signaling, and other poorly understood impacts of hyaluronan in cellular behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cell surface protrusions make contacts to extracellular matrix and other cells, sense and interact with the environment, and lead to new attachment sites and cell migration (1). Hyaluronan synthesis increases the migration rate of different cell types (17)(18)(19), but it is currently not known which type of protrusions are involved. The present finding that hyaluronan tethered to plasma membrane strongly promotes cell surface protrusions offers a novel view to a number of previous reports indicating that hyaluronan stimulates cellular locomotion, multidrug resistance, ErbB2 signaling, and other poorly understood impacts of hyaluronan in cellular behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the HAS genes enhances the motility of a human melanoma cell line (20), and antisense suppression of HAS2 gene expression reduced keratinocyte migration (21). Important roles for the Ras signaling pathway in HA-dependent cell migration have been demonstrated by disruption of the HAS2 gene (22), and our recent study further indicated that simultaneous activation of Ras-mitogen-activated protein (MAP) kinase and PI3-kinase pathways is required for the activation of HA-dependent cell locomotion (16).…”
Section: Discussionmentioning
confidence: 99%
“…Of the three genes, particularly HAS2 is subject to regulation by growth factors, cytokines, and hormones (4,14,15). In keratinocyte cultures, EGF, keratinocyte growth factor, TNF␣, and retinoic acid induce, whereas TGF␤ inhibits, HAS2 expression (8,10,13,16). Accordingly, the HAS2 promoter has been shown to contain functional response elements (REs) 3 for different transcription factors, including retinoid acid receptor, NF-B, CREB1 (cAMP response elementbinding protein 1), and SP1 (specificity protein 1) (7,11,16).…”
mentioning
confidence: 99%
“…Changes in hyaluronan production have been associated mostly with the expression level of HAS genes (3-6), especially in keratinocytes (7)(8)(9)(10)(11)(12)(13). Of the three genes, particularly HAS2 is subject to regulation by growth factors, cytokines, and hormones (4,14,15).…”
mentioning
confidence: 99%